2012
DOI: 10.1103/physrevlett.109.086101
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Map for Self-Organized Phase Separation during Film Deposition

Abstract: Drastically different two-phase microstructures have been reported for alloy epitaxial films, including self-organized nanoscale concentration modulations of vertical and lateral stripes. To understand the disparity of these microstructures, we study their formation mechanisms via spinodal decomposition during film deposition with the aid of computer simulations. Based on the simulation results, a microstructure map is established that describes relationships among the morphology of self-organized two-phase mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 44 publications
4
38
0
Order By: Relevance
“…When the diffusion along the surface is dominant, the film tends to form cylinder or columnar structures perpendicular to the growth plane as diffusion is confined in the top layers, whereas the subsurface interdiffusion (diffusion normal to the surface (z-direction)) is negligible. Lu et al have developed a phase-field-model of SD in epitaxial films and established the relationship among morphologies of two-phase microstructure, alloy composition, and deposition rate with the aid of computer simulations [29]. According to their simulations results, the lateral composition modulation develops at a slower deposition rate relative to the phase separation process in the films which is also consistent with the simulation results reported in Ref.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…When the diffusion along the surface is dominant, the film tends to form cylinder or columnar structures perpendicular to the growth plane as diffusion is confined in the top layers, whereas the subsurface interdiffusion (diffusion normal to the surface (z-direction)) is negligible. Lu et al have developed a phase-field-model of SD in epitaxial films and established the relationship among morphologies of two-phase microstructure, alloy composition, and deposition rate with the aid of computer simulations [29]. According to their simulations results, the lateral composition modulation develops at a slower deposition rate relative to the phase separation process in the films which is also consistent with the simulation results reported in Ref.…”
Section: Resultssupporting
confidence: 73%
“…On the other hand, when the growth rate is higher, the composition variation occurs in the direction normal to the film plane. This phenomenon, called surface-directed spinodal decomposition (SDSD), generates the superlattice structure in the film after phase separation [17,29]. In our previous study, we reported the superlattice structure formation through SDSD in SrTiO 3 films grown by Dynamic Aurora PLD [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plan-view sample of the Mo-rich matrix exhibits a bicontinuous morphology as shown in Figure 3(d). This morphology is expected when the spinodal decomposition outruns the deposition process [20]. As a fresh layer is deposited, the existing layer has already decomposed, which serves as a template for the decomposition of the fresh layer, resulting in a structure as shown in Figure 3(e).…”
Section: Nanocomposite With Coarse-length-scale Bicontinuous Zonesmentioning
confidence: 99%
“…6 and 20. Similar developments can be applied for various phenomena described by the phase field approach, such as various phase transformations (martensitic, 1,6,20 reconstructive, 21 and electromagnetic phase transformations, 22 melting-freezing, 7,23 amorphization), diffusive phase transformations described by Cahn-Hilliard theory (e.g., spinodal decomposition, segregation, separation, and precipitation), 24 twinning, 20,25 grain evolution, 26 dislocations, 27 fracture, 28 and interaction of defects (cracks and dislocations) and phase transformations. 29 Finally, the expression obtained for the surface stresses can be included in commercial multyphysics codes, like COSMOL, 30 instead of the current simplified expressions.…”
Section: Discussionmentioning
confidence: 99%